2009
DOI: 10.3168/jds.2009-2152
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon increases hepatic mRNA concentrations of ureagenic and gluconeogenic enzymes in early-lactation dairy cows

Abstract: Exogenous glucagon increases hepatic glucose synthesis in part by increasing hepatic extraction of amino acids from blood for conversion to glucose. To examine the role of glucagon in orchestrating gene expression of gluconeogenic and ureagenic enzymes, we determined the mRNA concentrations of key hepatic ureagenic and gluconeogenic enzymes at d 11, 15, and 22 postpartum in multiparous Holstein cows that received 0 or 5 mg of glucagon in 60 mL of saline by subcutaneous injection every 8 h for 14 d starting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(69 reference statements)
3
20
0
Order By: Relevance
“…In contrast, PCK1 mRNA expression has increased as DM intake (Greenfield et al, 2000) and ruminal propionate (Karcher et al, 2007) increased in dairy cow in early lactation. However, similar to our results, and in agreement with the negative correlation between plasma insulin and PCK1 mRNA reported here, others (She et al, 1999;Bobe et al, 2009) have observed a decreased expression of this transcript in dairy cows with greater glucose and insulin, and lower glucagon concentrations. On the other hand, while we did not detect differences in hepatic PC mRNA due to cattle supplementation, it has been reported that its expression increased in early-lactation dairy cows linked to reduced insulin-to-glucagon ratio (Greenfield et al, 2000;Bobe et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast, PCK1 mRNA expression has increased as DM intake (Greenfield et al, 2000) and ruminal propionate (Karcher et al, 2007) increased in dairy cow in early lactation. However, similar to our results, and in agreement with the negative correlation between plasma insulin and PCK1 mRNA reported here, others (She et al, 1999;Bobe et al, 2009) have observed a decreased expression of this transcript in dairy cows with greater glucose and insulin, and lower glucagon concentrations. On the other hand, while we did not detect differences in hepatic PC mRNA due to cattle supplementation, it has been reported that its expression increased in early-lactation dairy cows linked to reduced insulin-to-glucagon ratio (Greenfield et al, 2000;Bobe et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…However, similar to our results, and in agreement with the negative correlation between plasma insulin and PCK1 mRNA reported here, others (She et al, 1999;Bobe et al, 2009) have observed a decreased expression of this transcript in dairy cows with greater glucose and insulin, and lower glucagon concentrations. On the other hand, while we did not detect differences in hepatic PC mRNA due to cattle supplementation, it has been reported that its expression increased in early-lactation dairy cows linked to reduced insulin-to-glucagon ratio (Greenfield et al, 2000;Bobe et al, 2009). These contrasting results on the expression of PCK1 and PC mRNA in the liver could be the result of the animal model (dairy cows vs. beef heifers) used as well as animal energy balance (negative vs. positive) and physiological function (milk production vs. tissue deposition).…”
Section: Discussionsupporting
confidence: 94%
“…Postpartum ESB supplementation elevated (P < 0.05) glucagon concentration for LED cows throughout the first 8 wk of lactation and for MED cows at 14 d relative to parturition (Table 4; Figure 1). Glucagon promotes gluconeogenesis and increases the mRNA expression of gluconeogenic enzymes in liver of early lactating cows (Bobe et al, 2009), and it is used to prevent or treat fatty liver disease in dairy cattle (Bobe et al, 2003;Nafikov et al, 2006). The increased glucagon concentration in cows receiving the TRT diet indicated an improved gluconeogenic status and may be related to the increased production of milk and lactose.…”
Section: Dmi Bsc and Ebmentioning
confidence: 99%
“…Arginine is used to assess beta cell function but also increases glucagon secretion (35) whereas the branch-chained amino acids (BCAAs); leucine, isoleucine, and valine, to our knowledge have not been reported to stimulate glucagon secretion (17,33,52), with the exception of a single study in which a 20 min valine and leucine stimulation increased glucagon secretion in the perfused rat pancreas (3). By acting on its hepatic seven transmembrane receptor, the glucagon receptor (Gcgr), glucagon increases the hepatic uptake and metabolism of amino acids (5,22,24,25,28,45,47,49,56,63). In line with this, pathologically increased plasma concentrations of glucagon (e.g.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%